RETRACTED: Case Report: Treatment of Hypertrophic Cardiomyopathy With Stereotactic Body Radiotherapy - Xiao, Longzihui; Liu, Jiayi; Zhang, Yingzhe; Liu, Yuefei; Tang, Yan; Zhang, Minping; Ding, Zhuyuan; Xiao, Enhua; Chen, Taili (Frontiers in Medicine, 2022)
We report the novel treatment of hypertrophic cardiomyopathy (HCM) using stereotactic body radiotherapy (SBRT) with 25 Gy in 1 fraction in a 71-year-old man, which improved his quality of life. No toxicity occurred during or immediately after treatment. Our observations suggest that SBRT may be a reasonable treatment approach for HCM patients not indicated for surgery.